EARLY DIAGNOSTIC CRITERIA OF THE RENAL GRAFT REJECTION CRISIS ACCORDING TO THE ULTRASOUND MONITORING - V. A. Sandrikov; M. M. Kaabak; E. N. Platova; V. I. Sadovnikov; N. N. Babenko; A. K. Zokoev (Трансплантология (Москва), 2017)
.